Application of Advanced Exergetic Analysis for the Improvement of Chemical Processes. Issue 5 (31st March 2017) - Penkuhn, Mathias; Tsatsaronis, George
Abstract: The exergy concept addresses the synthesis, design, and optimization of processes in which matter and energy are converted. While a conventional exergy analysis identifies the location, magnitude, and causes of thermodynamic inefficiencies within a system, the concept of advanced exergetic analysis provides the opportunity to reveal the structural interdependencies of the system components and to estimate the thermodynamic improvement potential of the most components. The capabilities of an advanced exergetic analysis are demonstrated using the hydrodealkylation process of toluene as an example. Abstract : Identifying potential improvement options is a crucial task for optimizing energy‐intensive chemical processes. Using the information provided by an advanced exergetic analysis it is possible to identify the structural interdependencies and the improvement potential of system components.